2015
DOI: 10.1021/acs.est.5b01449
|View full text |Cite
|
Sign up to set email alerts
|

Single Exposure to near Roadway Particulate Matter Leads to Confined Inflammatory and Defense Responses: Possible Role of Metals

Abstract: Inhalation of traffic-associated atmospheric particulate matter (PM2.5) is recognized as a significant health risk. In this study, we focused on a single ("subclinical response") exposure to water-soluble extracts from PM collected at a roadside site in a major European city to elucidate potential components that drive pulmonary inflammatory, oxidative, and defense mechanisms and their systemic impacts. Intratracheal instillation (IT) of the aqueous extracts induced a 24 h inflammatory response characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
2
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 50 publications
3
66
2
2
Order By: Relevance
“…Although previous epidemiological and ambient studies have found correlations between metals and various measures of health effects (Verma et al, 2010;Pardo et al, 2015;Burnett et al, 2001;Huang et al, 2003;Akhtar et al, 2010;Charrier and Anastasio, 2012), the measured levels of TNF-α, IL-6, and ROS/RNS obtained in this study demonstrate that organic aerosols alone can induce a cellular response. This was previously observed for the oxidative potential as measured by DTT activity as well, where the same laboratory-generated organic aerosol samples catalyzed redox reactions and resulted in measurable DTT decay in the absence of metal species (Tuet et al, 2017).…”
Section: Discussioncontrasting
confidence: 77%
“…Although previous epidemiological and ambient studies have found correlations between metals and various measures of health effects (Verma et al, 2010;Pardo et al, 2015;Burnett et al, 2001;Huang et al, 2003;Akhtar et al, 2010;Charrier and Anastasio, 2012), the measured levels of TNF-α, IL-6, and ROS/RNS obtained in this study demonstrate that organic aerosols alone can induce a cellular response. This was previously observed for the oxidative potential as measured by DTT activity as well, where the same laboratory-generated organic aerosol samples catalyzed redox reactions and resulted in measurable DTT decay in the absence of metal species (Tuet et al, 2017).…”
Section: Discussioncontrasting
confidence: 77%
“…gov/urban-air-toxics/urban-air-toxic-pollutants; last access: 1 August 2018). Depending on the aerosol composition, extent and time of exposure, previous studies have confirmed that most elemental components of fine particles (PM 2.5 ; particulate matter with aerodynamic diameter equal to or less than 2.5 µm) exert a multitude of significant diseases from pulmonary inflammation, to increased heart rate variability, to decreased immune response (Fergusson, 1990;Morman and Plumlee, 2013;Leung et al, 2008;Hu et al, 2012;Pardo et al, 2015;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have examined that the two exposure ways might easily damage the organisms (Pardo et al, 2015;Tsuji et al, 2015). Fig.…”
Section: Bde209 Accumulation In E Fetida After a Step And Repeated Ementioning
confidence: 99%